Detorsion of twisted (Gangrenous) ovarian cyst followed by complete disappearance of the cyst-a case report of innovative outcome - Shabbir, Ahmad Sheikh; Mainul, Haque; Roziana, Ramli (2015)
Adnexal torsion in the pediatric and adolescent population is a rare gynecological disease with an incidence of 2.7%. They are categorized by different clinical presentations and by the need to establish a suitable type and timing of treatment in order to prevent problems, such as ovarian necrosis after torsion and infertility. Ovarian torsion denotes a real surgical emergency. Quick diagnosis is crucial for ovarian salvage, and high clinical notion is imperative in this respect. Confounding the diagnosis in overall are more usually come across abdominal complaints in the Emergency Department (ED) such as constipation, diarrhea, and urinary tract infections and more common surgical emergencies such as appendicitis. Until a decade ago,the standard recommended treatment for ovarian torsion was removal of the gangrenous ovary without detorsion. However, conservative management for preservation of ovarian function should be undertaken because most females with adnexal torsion are adolescent girls and of childbearing age. A 10-year-old obese girl presented with a 3-days history of right iliac fossa pain. She was operated for acute appendicitis; however, intraoperatively found gangrenous twisted right ovarian cyst measuring 10x6 cm. Detorsion was done and noted the right fallopian tube appeared to be viable within few minutes however the right ovarian cyst remained the same. The postoperative period was uneventful. The same gangrenous ovary was monitored through repeated ultrasound examinations during follow-up visits and found that cyst was gradually decreasing in size and finally disappeared within 3 months. Detorsion of twisted ovarian cyst (conservative management) leads to complete disappearance and ovary not only be saved but also operative morbidity of interval cystectomy was avoided.